Effect of Serendipity in an Encounter on Purchase Intention of Unexpected Products - Liang, Shichang; Chu, Yuxuan; Zhang, Min; Li, Rulan; Lan, Bin; He, Lingling (Frontiers in Psychology, 2022)
Previous studies on the follow-up effect of serendipity mostly focused on the positive effects and less on the negative effects. Therefore, this article discusses the negative effect of serendipity on the purchase intention of unexpected products. Three experimental results showed that serendipity contains a certain degree of uncertainty, which will cause consumers’ perceived risk and decrease the purchase intention of unexpected products. Perceived risk plays a mediating role in the effect of serendipity on the purchase intention of unexpected products. Moreover, regulatory focus moderates the effect of serendipity on purchase intention of unexpected products. Specifically, for prevention-focused individuals, the negative effect of serendipity on the purchase intention of unexpected products is strengthened. For promotion-focused individuals, the negative effect of serendipity on the purchase intention of unexpected products is weakened. This article provides theoretical guidance and support for management practice in the field of marketing.